2015
DOI: 10.1177/1357633x15595556
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and telemedicine consultation of fetal urologic disorders

Abstract: In Arkansas, telemedicine is used commonly in obstetrics through Antenatal and Neonatal Guidelines, Education and Learning System (ANGELS), the existing statewide telemedicine network. This network is used primarily for tele-ultrasound and maternal-fetal medicine consultation. This study is a retrospective case series, describing all the patients who had a prenatally diagnosed urologic anomaly that required prenatal urologic consultation. From 2009-2013, approximately 1300 anomalies were recorded in the Arkans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Prior to the COVID-19 pandemic, telemedicine was an under-utilized form of delivering health care in the field of pediatric urology [ 10 ]. Prior studies have demonstrated successful telemedicine encounters for post-operative visits as well as for prenatal consultations on urologic conditions, most commonly including urinary tract dilation [ [5] , [6] , [7] ]. Out of necessity, the pandemic has changed the way practitioners have traditionally provided services in order to maintain quality care for pediatric urologic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the COVID-19 pandemic, telemedicine was an under-utilized form of delivering health care in the field of pediatric urology [ 10 ]. Prior studies have demonstrated successful telemedicine encounters for post-operative visits as well as for prenatal consultations on urologic conditions, most commonly including urinary tract dilation [ [5] , [6] , [7] ]. Out of necessity, the pandemic has changed the way practitioners have traditionally provided services in order to maintain quality care for pediatric urologic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine allows for the delivery of care while maintaining safe social-distancing measures. Remote video visits (VVs) have been used successfully for years in pediatric urology for the delivery of postoperative care [5,6] and prenatal urologic consultation [7]. Yet overall, there is a paucity of existing research on the use of telemedicine for general pediatric urologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine has been used sparingly in the United States for the management of pediatric urologic patients post-surgery and for follow-up of medical conditions like enuresis. No evidence exists in the literature in this country examining its potential utility in the preoperative setting in urology (6)(7)(8)(9). In addition to reports of management of medical diseases and postoperative follow-up, prior studies in Canada and Australia have demonstrated utilization of telemedicine in preoperative care in a standard clinic-to-clinic telehealth model.…”
Section: Discussionmentioning
confidence: 99%
“…The distance required for in-person evaluation of pediatric urologic diseases can be economically and logistically challenging for patients and families. Consequently, our urology division implemented a telemedicine program almost 10 years ago and has reported the feasibility of telemedicine in multiple areas, such as postoperative evaluation, prenatal consultation, and follow-up management of enuresis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the pandemic, there had been marginal interest in expanding the usage of telemedicine in the United States, including in specialities such as pediatric urology. Telemedicine was not widely used by pediatric urologists prior to the COVID-19 pandemic with only a few examples demonstrating its utility for postoperative evaluations (2,3), prenatal consultations (4), and management of enuresis (5). As in many other specialties, pediatric urologists were forced to rapidly increase usage of this type of patient care due to restrictions linked to the pandemic (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%